Heteroannulation enabled by a bimetallic Rh(iii)/Ag(i) relay catalysis: application in the total synthesis of aristolactam BII. Issue 41 (10th May 2017) - Ji, Wei-Wei; Lin, E.; Li, Qingjiang; Wang, Honggen
Abstract : A Rh(iii )/Ag(i ) relay catalysis allowed the construction of 3-alkylidene isoindolinones and 3-alkylidene isobenzofuranones. The synthetic application in the total synthesis was accomplished. Abstract : A redox-neutral bimetallic Rh(iii )/Ag(i ) relay catalysis allowed the efficient construction of 3-alkylidene isoindolinones and 3-alkylidene isobenzofuranones. The Rh(iii ) catalyst was responsible for the C–H monofluoroalkenylation reaction, whereas the Ag(i ) salt was an activator for the follow-up cyclization. The methodology developed was applied as a key step in the rapid total synthesis of the natural product aristolactam BII.